2012
DOI: 10.1155/2012/204657
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of Left Circumflex Artery Detected by Computed Tomography Coronary Angiography: A Case Report

Abstract: The congenital absence of the left circumflex artery (LCx) is a very rare congenital anomaly of coronary arteries, but it is benign. Currently, the best modality for the diagnosis of coronary anomalies is computed tomography coronary angiography (CTCA). We report a case of congenitally absent LCx with an atypical chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…(7) Congenitally absent left circumflex artery is an extremely rare anomaly of coronary arteries with only a small number of cases having been reported, but its incidence is increasing due to the wide use of MDCT Coronary angiography. (8,9) (Fig. 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(7) Congenitally absent left circumflex artery is an extremely rare anomaly of coronary arteries with only a small number of cases having been reported, but its incidence is increasing due to the wide use of MDCT Coronary angiography. (8,9) (Fig. 1).…”
Section: Discussionmentioning
confidence: 96%
“…2), interarterial or preaortic course, anterior or prepulmonic course and septal or subpulmonic course. (9,10) The left main coronary artery or left anterior descending artery arising from the right coronary sinus of Valsalva and right coronary artery originating from the left coronary sinus of Valsalva may be associated with sudden cardiac death, hence deserve special attention. (6) Anomalous origin of the left coronary artery from the pulmonary trunk (ALCAPA), also known as Garland-BlandWhite syndrome, is an extremely rare but potentially fatal congenital cardiovascular anomaly with an incidence of 1 in 300,000 live births.…”
Section: Discussionmentioning
confidence: 99%
“…Congenitally absent LCX is a very rare anomaly and not many cases have been reported. Its reported incidence is between 0.003% [50] and 0.067% [24] . This anomaly is considered a benign condition in the absence of coronary occlusive disease, however it can cause angina-like symptoms, particularly on exertion.…”
Section: Congenital Absence Of Lcxmentioning
confidence: 99%
“…It is hypothesized that "steal phenomenon" could explain symptoms, where increased metabolic demand in the LCX territory would cause ischaemia in the LAD or RCA territories. Hongsakul et al [50] reported a case of absent LCX in a 52yearold man with acute chest pain and palpitations. Multiple enlarged diagonal branches of LAD were present to supply the lateral wall of LV in addition to a super-dominant RCA with its posterolateral branch continuing into the territory of the LCX [24,50] .…”
Section: Congenital Absence Of Lcxmentioning
confidence: 99%
“…The aetiology of symptoms is not exactly known, but a ‘steal phenomenon’ appears as the most probably hypothesis. The detection of congenitally absent LCx is necessary because some patients have symptoms that are similar to those who have coronary disease 7 8…”
Section: Discussionmentioning
confidence: 99%